Pengaruh Media Flashcard Terhadap Kemampuan Menulis Permulaan Siswa Kelas I SDN 104200 Desa Karang Gading Labuhan Deli - Chadijah, Siti; Harahap, Syarifah Ainun; Ramadhani, Mastari (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This research aims to determine the effect of flashcard media on the essay writing ability of first-grade students at SDN 104200 Karang Gading Village Labuhan Deli. An experimental design was employed with two groups: an experimental group taught using flashcard media and a control group taught using conventional methods. The Kolmogorov-Smirnov normality test results showed that the pre-test and post-test scores of both groups were normally distributed. The experimental group showed significant improvement in writing ability, with Exact Sig. (2-tailed) values of 0.000 < 0.05, indicating the acceptance of H1. Similarly, the control group showed improvement with Exact Sig. (2-tailed) values of 0.000 < 0.05, confirming the effectiveness of conventional methods. However, flashcard media was found to have a greater influence on the students’ writing abilities compared to conventional methods. These findings suggest that flashcard media can be an effective tool to enhance early writing skills in elementary education.